PENGEMBANGAN PROTOTYPE PERMAINAN EDUKASI BERDASARKAN PENERAPAN PRINSIP MONTESSORI UNTUK MENINGKATKAN PENGETAHUAN PROFESI DENGAN PENGUJIAN TAM - Susanto, William (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Educational games is one of the types of information technology oriented entertainment and learning. Educational games has become one of the learning tools that can improve cognitive and psychomotor. This study aims to develop and test prototype educational games to guess the profession. Critical theory used is the Montessori method and technology acceptance models. The results of this research is the development of a prototype that contains learning to improve the diversity of knowledge profession. The result of the research obtained in this study are: (a) Prototype educational games to guess the profession can improve students' knowledge of the diversity of the profession, (b) Students receive a well where a prototype , and (c) Assessment of the effect between the variables of perceived ease of use, perceived usefulness and behavioral intention to find out the desire of the students in the use of prototype educational games to guess the profession. Key words metode Montessori, permainan edukasi, technology acceptance model, prototype